Implementing the Paris Declaration on aid effectiveness: where does Germany stand? - Guido Ashoff (Deutsches Institut für Entwicklungspolitik (DIE), 2008)
The Paris Declaration (PD), adopted in 2005, lays down principles and procedures for enhancing the effectiveness of aid and specifies them in twelve targets supplied with monitorable indicators and to be achieved by 2010. The PD thereby clearly enlarges the international regulatory framework (norms, standards) of development cooperation. The PD complements the international commitments regarding the global development goals and scaling up financial resources for development. According to the PD, partner countries (supported by donors) are to create the basis for effective aid by assuming ownership, elaborating operational development strategies through broad consultative processes, establishing reliable public financial systems and coordinating all donor contributions. Donors commit to respecting partner country leadership, aligning their overall support with partners' priorities, strategies, capacities and procedures, and harmonising their approaches. Both sides are jointly responsible for the resultsoriented management of their efforts and accountable for development results. The quantitative assessment by the OECD of the progress towards 2010 reveals considerable delays of partner countries. Germany, while having advanced and partly being ahead of the donor average, has yet to make further efforts to achieve the targets by 2010. A qualitative evaluation of Germany's implementing the PD, conducted by DIE, shows that there is a high commitment being made to the PD and it is perceived as important. The institutional capacity to implement the PD has been improved by a number of measures. At the systemic level of German development cooperation, there are factors that both facilitate and hamper implementing the PD.
Keywords: 330